A panel of blood-based circulatory miRNAs with diagnostic potential in patients with psoriasis - Madaan, Priyanka; Sharma, Uttam; Tyagi, Nipanshi; Brar, Balvinder Kaur; Bansal, Shivani; Kushwaha, Hemant Rituraj; Kapoor, Harmanpreet Singh; Jain, Aklank; Jain, Manju (Frontiers in Medicine, 2023)
Psoriasis is a chronic inflammatory skin disease with keratinocyte hyperproliferation and T cells as crucial mediators of lesional and systemic inflammatory changes. Till date, no amenable differential biomarkers are available for the disease diagnosis. More recently, microRNAs are understood as critical regulators of lesional and systemic immune changes in psoriasis with diagnostic potential. We have performed expression profile of T cell specific miRNAs in 38 plasma samples from psoriasis vulgaris patients and equal number of age, sex matched healthy subjects. Our findings have identified a panel of 5 blood-based circulatory miRNAs with significant change in their expression level comprising miR-215, miR-148a, miR-125b-5p, miR-223 and miR-142-3p that can differentiate psoriasis vulgaris patients from healthy individuals. Receiver operating characteristic (ROC) curves for all the 5 miRNAs individually as well as in combination exhibited a significant disease discriminatory area under the curve with AUC = 0.762 and p< 0.0001 for all the miRNAs together. Statistically, all 5 miRNAs in combination depicted the best-fit model in relation with disease severity (PASI) compared to individual miRNAs with highest R 2 value = 0.94 and least AIC score =131.8. Each of the miRNA also exhibited a significant association with at least one of the other miRNAs in the panel. Importantly, the 5 miRNAs in the panel regulate one or more immune-inflammation pathways based on target prediction, pathway network analysis and validated role in literature. The miRNA panel provides a rationalized combination of biomarkers that can be tested further on an expanded cohort of patients for its diagnostic value.